Language Complexity in Historical Perspective: The Enduring Tropes of Natural Growth and Abnormal Contact - McElvenny, James (Frontiers in Communication, 2021)
Focusing on the work of John McWhorter and, to a lesser extent, Peter Trudgill, this paper critically examines some common themes in language complexity research from the perspective of intellectual history. The present-day conception that increase in language complexity is somehow a ``natural'' process which is disturbed under the ``abnormal'' circumstances of language contact is shown to be a recapitulation of essentially Romantic ideas that go back to the beginnings of disciplinary linguistics. A similar genealogy is demonstrated for the related notion that grammatical complexity is a kind of ``ornament'' on language, surplus to the needs of ``basic communication''. The paper closes by examining the implications of these ideas for linguistic scholarship.